Arsitektur Dalam Konteks Estetika - Tri Prasetya Utomo (Ornamen, 2007)
Aesthetics may be defined narrowly as the theory of beauty, or more broadly as that together with the philosophy of art. Traditionally, the philosophy of art concentrated on its definition, but recently this has not been the focus, with a careful analyses of aspects of art largely replacing it. Philosophical aesthetics is here considered to center on these latter- day developments. Some aesthetic effects available in architecture include tonal variation, repetition, field effects, symmetry/asymmetry, perceived mass, subliminal structure, linear dynamics, tension and repose, pattern, contrast, perspective, 3 dimensionality, movement, rhythm, unity/Gestalt, matrixiality and proportion Generally, architecture adheres to the aesthetic principles of symmetry/asymmetry, focal point, pattern, contrast, perspective, 3D dimensionality, movement, rhythm, unity/gestalt, and proportion.Key word : aesthetic and architecture.